Searching for Solid Ground in Polish-American Relations in the Second Year of the Trump Administration - Szklarski, Bohdan; Ilowski, Piotr (International Studies. Interdisciplinary Political and Cultural Journal, 2019)
Since the beginning of the Trump Administration, analysts of American foreign policy have observed several changes in the style substance and style of Washington’s international behavior with regard to both foes and friends. President Trump in his rhetoric (including social media communication) and style represent a disturbing discontinuity, especially for allies that undermines the stability of American international commitments. American allies are forced to develop new strategies for managing this new risk in relations with Washington. This paper examines the tactics employed by the government in Warsaw in that regard.